Предмет: Алгебра,
автор: nikitahova
(x-7)^2+3=(x-2)•(x+2)
Ответы
Автор ответа:
0
х^2-14х+49+3=х^2-4
х^2-14х+49+3-х^2+4=0
-14х+56=0
х^2-14х+49+3-х^2+4=0
-14х+56=0
Автор ответа:
0
Все изи
С переменной x переносим все в лево, а без Нее в право, и дальше находим сам x
С переменной x переносим все в лево, а без Нее в право, и дальше находим сам x
Приложения:
Похожие вопросы
Предмет: Химия,
автор: stassuprun3
Предмет: Алгебра,
автор: disah087
Предмет: Математика,
автор: maslakvadik318
Предмет: Геометрия,
автор: roza20051350